PERCUTANEOUS CORONARY INTERVENTION IN UN-PROTECTED LEFT MAIN CORONARY ARTERY DISEASE - A CASE REPORT - Naeem Asghar (Journal of University Medical & Dental College, 2017)
INTRODUCTION: By convention, significant LMCA stenosis is treated by coronary artery bypass graft (CABG) surgery. However, with the advancement in interventional tools, operators’ expertise, pharmaceuticals and supportive measures, outlook regarding left main PCI is changing.